A novel flexible piezoresistive sensor using superelastic fabric coated with highly durable SEBS/TPU/CB/CNF nanocomposite for detection of human motions. (18th August 2022) - Chen, Tianjiao; Wu, Guanzheng; Panahi-Sarmad, Mahyar; Wu, Yutong; Xu, Runxin; Cao, Shaojie; Xiao, Xueliang
Abstract: Piezoresistive sensors have profusely permeated our lives nowadays and drawn a great deal of attention because of their facile fabrication, appropriate flexibility, and excellent sensitivity. However, the combination of elastic fabric and conductive coatings, due to coating quality and their interaction with the fabric matrix, is still challenging. Here, a kind of sensitive and durable piezoresistive sensors based on knitted fabric decorated with a composite coating of carbon black (CB), cellulose nanofiber (CNF), thermoplastic polyurethane (TPU), and thermoplastic elastomer styrene-ethylene/butylene-styrene (SEBS) were fabricated via solution blending assisted with ultrasonication and dip coating. The chemical analysis indicates strong interactions have been constructed by CNF between coating and fabric, which improve mechanical durability and stability. The as-prepared sensor displayed pressure sensing sensitivity of 0.0316 kPa −1 (<15 kPa), a wide working range (>200 kPa), and exceptional stability (more than 1000 cycles). Eventually, the sensors were attached to different human body places for motion detection, and the testing results presented well. In a nutshell, this sensitive and stable flexible piezoresistive sensor is able to put a step ahead in smart wear and healthcare application. Graphical abstract: Image 1